2019
DOI: 10.3390/molecules24203679
|View full text |Cite
|
Sign up to set email alerts
|

Limonin: A Review of Its Pharmacology, Toxicity, and Pharmacokinetics

Abstract: Limonin is a natural tetracyclic triterpenoid compound, which widely exists in Euodia rutaecarpa (Juss.) Benth., Phellodendron chinense Schneid., and Coptis chinensis Franch. Its extensive pharmacological effects have attracted considerable attention in recent years. However, there is no systematic review focusing on the pharmacology, toxicity, and pharmacokinetics of limonin. Therefore, this review aimed to provide the latest information on the pharmacology, toxicity, and pharmacokinetics of limonin, explorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 104 publications
(108 reference statements)
0
56
0
Order By: Relevance
“…It has been reported for various biological activities like antiviral, antifungal, antibacterial, anticancer and antimalarial, etc. [ 38 , 39 , 40 ]. However, to our knowledge, there have been no reports on the application of limonin in reducing postharvest blue mold of citrus fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported for various biological activities like antiviral, antifungal, antibacterial, anticancer and antimalarial, etc. [ 38 , 39 , 40 ]. However, to our knowledge, there have been no reports on the application of limonin in reducing postharvest blue mold of citrus fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the addition of a low dose of limonin to EG nanoemulsion could significantly improve the antifungal activity against P. italicum in vitro, suggesting that limonin and eugenol played a synergistic effect. Limonin has been reported to interfere with the transmission of signals between microbial cells and effectively inhibit intercellular communication [ 39 ]. Therefore, limonin probably reduced the adaptability of fungal cells to external pressures and enhance their sensitivity to eugenol.…”
Section: Discussionmentioning
confidence: 99%
“…Limonin is a secondary metabolite with high biological activity in plants. It is present mainly in the fruits of Rutaceae plants, such as navel oranges, citruses, oranges, and grapefruits (Zhang et al, 2015;Wang et al, 2018c;Fan et al, 2019). The content in the core (seed) of the fruit is higher, while the content in the peel is low.…”
Section: Terpenoidsmentioning
confidence: 99%
“…It is worth mentioning that the most abundant compound is limonin ( 1 ; 0.5 g), with 2.27 % yield in the crude AcOEt extract. Literature survey indicated that limonin has extensive pharmacological effects, [24] especially the anti‐inflammatory activity by the inhibition of TNF‐ α release, and the regulation of TLR4/NF‐ κ B pathway [25] . In order to obtain more limonin‐like compounds for further study of anti‐inflammatory activities, we have carried out a chemical transformation of limonin through reduction reactions with different reductants such as sodium borohydride (NaBH 4 ), sodium cyanoborohydride (NaBH 3 CN) and lithium aluminum hydride (LiAlH 4 ) [26] .…”
Section: Resultsmentioning
confidence: 99%